Caregiving burnout of community-dwelling people with dementia in Hong Kong and New Zealand: a cross-sectional study - Crystal Y. Chan; Gary Cheung; Adrian Martinez-Ruiz; Patsy Y. K. Chau; Kailu Wang; E. K. Yeoh; Eliza L. Y. Wong (BMC Geriatrics, 2021)
Abstract Background Informal caregiving for people with dementia can negatively impact caregivers’ health. In Asia-Pacific regions, growing dementia incidence has made caregiver burnout a pressing public health issue. A cross-sectional study with a representative sample helps to understand how caregivers experience burnout throughout this region. We explored the prevalence and contributing factors of burnout of caregivers of community-dwelling older people with dementia in Hong Kong (HK), China, and New Zealand (NZ) in this study. Methods Analysis of interRAI Home Care Assessment data for care-recipients (aged ≥65 with Alzheimer’s disease/other dementia) who had applied for government-funded community services and their caregivers was conducted. The sample comprised 9976 predominately Chinese in HK and 16,725 predominantly European in NZ from 2013 to 2016. Caregiver burnout rates for HK and NZ were calculated. Logistic regression was used to determine the adjusted odds ratio (AOR) of the significant factors associated with caregiver burnout in both regions. Results Caregiver burnout was present in 15.5 and 13.9% of the sample in HK and NZ respectively. Cross-regional differences in contributing factors to burnout were found. Care-recipients’ ADL dependency, fall history, and cohabitation with primary caregiver were significant contributing factors in NZ, while primary caregiver being child was found to be significant in HK. Some common contributing factors were observed in both regions, including care-recipients having behavioural problem, primary caregiver being spouse, providing activities-of-daily-living (ADL) care, and delivering more than 21 h of care every week. In HK, allied-health services (physiotherapy, occupational therapy and speech therapy) protected caregiver from burnout. Interaction analysis showed that allied-health service attenuates the risk of burnout contributed by care-recipient’s older age (85+), cohabitation with child, ADL dependency, mood problem, and ADL care provision by caregivers. Conclusions This study highlights differences in service delivery models, family structures and cultural values that may explain the cross-regional differences in dementia caregiving experience in NZ and HK. Characteristics of caregiving dyads and their allied-health service utilization are important contributing factors to caregiver burnout. A standardized needs assessment for caregivers could help policymakers and healthcare practitioners to identify caregiving dyads who are at risk of burnout and provide early intervention.